Step Level Procedure for Remaining Fatigue Life Evaluation of One Railway Bridge - Alessio Pipinato (The Baltic Journal of Road and Bridge Engineering)
Reliable structural integrity and remaining life assessment are essential for infrastructural ageing mitigation of. For example, as a consequence of the lack of new riveted steel bridges, less attention has been paid in order to deep the topic of fatigue strength behavior and in particular less research has been focused on the topic of the remaining fatigue life of riveted structure. As a consequence, a series of diagnostic tests were performed on one short-span, twolane, historical railway steel-girder bridge, in service from 1918. In this article are presented results concerning the step by step fatigue assessment of the bridge investigated: the safe condition of the bridge after almost a century service life period, apart from a dangerous failure mechanism have been evidenced, as confirmed by the analytical procedure and the experimental results reported.